Efektivitas penyuluhan gizi berbasis prinsip B2SA terhadap tingkat pengetahuan ibu dalam upaya pemenuhan gizi seimbang bagi balita - Puteri, Hidayatusy Syukrina; Kustiani, Ai; Astuti, Dewi Woro; Harvidea, Radella; Nurhartanto, Adhi (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Indonesia still faces the serious challenge of triple burden malnutrition, particularly in rural areas such as Hajimena Village, South Lampung. Limited access to nutrition information and suboptimal utilization of local foods are major obstacles to toddler feeding practices. The principle of Diverse, Nutritious, Balanced, and Safe Food (B2SA), as outlined in the